Grinding power model for flute grinding of solid tools based on equivalent chip thickness - Lei REN; Jiangtao PAN; Daohui XIANG; Junjin MA; Xiaobin CUI (Jin'gangshi yu moliao moju gongcheng)
ObjectivesDuring the flute grinding process of solid tools, the majority of grinding power is converted into grinding heat. Excessive grinding power can cause a rapid temperature rise on the surface of the contact area between the grinding wheel and the tool, which can easily lead to grinding burns and eventually tool failure. A grinding power model for flute grinding of solid tools is proposed based on equivalent chip thickness, aiming to achieve precise prediction and control of grinding power for flute grinding.MethodsA kinematic model for flute grinding is established using homogeneous coordinate transformation. On this basis, according to the theory of conjugate surfaces, the instantaneous contact line between the grinding wheel surface and the flute surface during the grinding process is obtained, and the grinding wheel is discretized into a set of equally thick grinding wheel slices. The grinding contact arc length is obtained by calculating the intersection points between the grinding wheel slices and the tool cylindrical surface. Flute grinding is regarded as external cylindrical grinding with a special contact zone shape. By introducing the contact-area-shape coefficient to define the equivalent grinding depth and the equivalent feed rate of each grinding wheel slice, the formula for calculating the equivalent grinding layer thickness of flute grinding is derived. When the linear speed of the grinding wheel, the axial feed speed of the workpiece, and the grinding contact arc length of each grinding wheel slice are known, the equivalent chip thickness of each grinding wheel slice can be calculated as long as the shape coefficient of the contact area is given. The cross-section profiles of the chute are discretized into small triangles, and the area of the cross-section profile of the chute is obtained by calculating the area of each triangle. The material removal rate of the chute during grinding is determined by combining the axial feed velocity of the workpiece. According to the principle of conservation of material removal rate, the formula for the shape coefficient of the contact area is derived. Based on the mathematical relationship between the local grinding power of each grinding wheel slice and the thickness of the equivalent grinding layer, the empirical model for flute grinding power is established. The experimental verification of the model is carried out on an ANCA MX7 CNC tool grinding machine. The flute with a spiral angle of 30° is ground on a cemented carbide rod with a metal-bonded diamond wheel. The spindle power data of the machine tool PLC is recorded using the data recording function of iGrind grinding software. The spindle power includes grinding power and spindle idle power, so grinding power is obtained by subtracting idle power from spindle power. Twenty sets of grinding experiments are carried out under different grinding parameters, and an overdetermined equation set is established by substituting the grinding power data of four sets of experiments into the power model. By solving this equation system, the two empirical constants in the model are obtained. Then, the grinding power model is used to predict the grinding powers of twenty sets of grinding experiments, and the predicted grinding powers are compared with the actual grinding powers.ResultsThe comparison results show that the predicted grinding powers are close to the actual grinding powers, and the maximum relative error of the predicted grinding power is less than 15%. The equivalent chip thickness of each wheel slice and the grinding power per unit width vary gradually along the width of the grinding wheel, and the maximum equivalent chip thickness and the maximum grinding power per unit width exist at the edge of the grinding wheel.ConclusionsThe proposed grinding power model based on equivalent chip thickness can precisely predict the grinding power during the flute grinding process of solid tools, and obtain the distribution of grinding power in the width direction of the grinding wheel. The grinding power can be precisely controlled by adjusting grinding parameters with this model, and the maximum equivalent chip thickness and the maximum grinding power per unit width exist at the edge of the grinding wheel during the grinding process of the chute, which will lead to non-uniform wear in the direction of the width of the grinding wheel.